"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Why so many women still take their husband’s last name - Duncan, Simon (The Conversation, 2020)
While some women may be actively involved in choosing their marital name, taking the man’s name remains the norm.
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; approches et analyses; cours; discipline; droit des femmes*; famille; histoire et politique; mariage; norvège; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques

Return of the 1950s housewife? How to stop coronavirus lockdown reinforcing sexist gender roles - Chung, Heejung (2020)
Alors que le virus COVID-19 se propage à travers le monde, de nombreux gouvernements ont fermé les écoles , les crèches et autres établissements de garde d'enfants. Avec de plus en plus de personnes travaillant à domicile , il est probable que de nombreuses familles se retrouveront dans une situation où les deux parents essaient de travailler depuis la table de la cuisine tout en essayant de faire l'école à la maison aux enfants . En plus des tâches ménagères habituelles, comme la cuisine et le ménage, ces tâches peuvent représenter une charge supplémentaire pour de nombreux parents à l'heure actuelle. Il est cependant probable que même si les deux parents sont désormais à la maison, une grande partie des tâches « domestiques » reposera toujours sur les épaules des femmes de la maison. Tout comme la ménagère des années 1950, les femmes devront non seulement préparer des repas savoureux, garder la maison propre et bien rangée et divertir les enfants, mais elles devront également faire tout cela tout en travaillant à domicile.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; charge mentale; conciliation famille-travail; covid-19; discipline; famille; pandémie; projet charge mentale; périodes historiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (Gouvernement en question(s), 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences